PROPOSTA DE MELHORIA DE TRAMITAÇÃO DE PROCESSOS PARA UMA INSTITUIÇÃO PÚBLICA DE ENSINO: O ESTUDO DE CASO CEFET-RJ - Vieira, Ana Paula Nunes (2013)
This study addresses the issue of the control of the processing of cases in a federal public institution of teaching, CEFET-RJ. Currently, the way it is performed such control presents problems not meeting the expectations of employees and customers. The present study aims to present a proposal for improvement of processing of cases that meets the needs of internal and external customers. The search can be classified as exploratory and descriptive. As to the means, we used the bibliographical research and case study. The research instrument was applied the questionnaire, so that participants could express their experiences and professional needs. By analyzing the results, it was found the main difficulties faced by federal public institution of education in control processes: no training, the lack of a map of activities, the information system that was not developed according to the needs of users and the lack of standardization and procedures manuals. Moreover, it was realized what factors could bring benefits for a more effective functioning. The relevance of this work is the presentation of a proposal for improvement that can bring a greater satisfaction of internal and external customers of the public institution of teaching and help all who seek to resolve questions relating to the process control of processes.